2018
DOI: 10.3892/mmr.2018.9312
|View full text |Cite
|
Sign up to set email alerts
|

Screening of exosomal miRNAs derived from subcutaneous and visceral adipose tissues: Determination of targets for the treatment of obesity and associated metabolic disorders

Abstract: Exosomal micro (mi)RNAs have been suggested to have important roles in abdominal obesity, and to be associated with metabolic alterations via posttranscriptional regulation of target genes. However, exosomal miRNA profiles in subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) have rarely been investigated. In the present study, microarray data were obtained from the Gene Expression Omnibus database with the following accession numbers: GSE68885 (exosomal miRNAs in SAT obtained from seven patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…A bioinformatic approach identified a total of 23 active microRNAs (miRNAs) and transcription factor regulatory pathways significantly associated with obesity-related inflammation [87]. Also, a set of exosomal miRNAs differentially expressed in abdominal obesity was associated with inflammation [88]. Overweight and obesity led to deregulation of circulating inflammatory miRNAs, which may contribute to the heightened inflammatory state associated with these conditions [89].…”
Section: Obesity and Associated Diseasesmentioning
confidence: 99%
“…A bioinformatic approach identified a total of 23 active microRNAs (miRNAs) and transcription factor regulatory pathways significantly associated with obesity-related inflammation [87]. Also, a set of exosomal miRNAs differentially expressed in abdominal obesity was associated with inflammation [88]. Overweight and obesity led to deregulation of circulating inflammatory miRNAs, which may contribute to the heightened inflammatory state associated with these conditions [89].…”
Section: Obesity and Associated Diseasesmentioning
confidence: 99%
“…These studies have focused on the identification, expression, and function of miRNAs in adipose tissues of different anatomical depots [2125], and these findings have helped to elucidate the molecular mechanisms underlying adipose tissue development in animals. However, previous studies were limited to humans, mice and a few agricultural animals, as well as metabolic diseases, such as obesity [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of several adipocyte-derived exosomal miRNAs was altered in obese patients, and most of them were specific to the VAT or sWAT. Exosomal miRNAs derived from VAT were predicted to target mRNAs mainly involved in TGF-β and Wnt/β-catenin signaling [25,320]. Another study on circulating miRNAs in obese patients showed that miR-130b in serum was positively correlated with BMI (Figure 5).…”
Section: Exosomal Micrornas As Novel Adipokinesmentioning
confidence: 99%